CORRUPTION IN ACCESS TO EDUCATIONAL INSTITUTIONS - Jordan Deliversky (Peytchinski Publishing, 2016)
Education is universally valued as a formative condition of human and national development. Corruption not only distorts access to education but also affects the quality of education and the reliability of academic research findings. Corruption risks can be found at every level of education and research systems. Corruption in education has adverse implications for educational quality and learning outcomes. Financial fraud remains a major challenge for universities. The lack of academic integrity can also lead to corruption practices. The ingredients of good university governance can be used for combating corruption. Better management, good governance and oversight of funds in traditionally vulnerable areas, could help reduce financial fraud in education system.